Influence of Fertilization and Mycorrhizae on the Nutritional Status of Rhododendron (Rhododendron hybridum) in a Nursery - Zbigniew Jarosz; Zenia Michałojć; Karolina Pitura; Katarzyna Dzida; Michał Koter (Agriculture, 2021)
Background: This study of the large-flowered azalea cv. ‘Anneke’ investigated the impact of two factors, i.e., methods of fertilization and mycorrhization, on the nutritional status of plants during three years of nursery cultivation. Methods: Single mineral fertilizers, a slow-release fertilizer Hortiform pH (SRF), and fertigation in combination with mycorrhization of plants, were applied. Plant roots were inoculated with fungi from the genera Oidiodendron and Hymenoscyphus sp. The nutritional status of the large-flowered azalea in the first three years of cultivation was assessed based on macroelements. Results: The analyses revealed significantly higher content of nitrogen, phosphorus and calcium in the leaves of plants inoculated with fungal mycelium. A beneficial effect of plant mycorrhization on plant nutritional status, i.e., higher levels of nitrogen, phosphorus, potassium, calcium, and magnesium, was noted in the second and third years of azalea cultivation. Conclusions: Significant amounts of the nutrients were utilized in the middle of the growing season and almost fully utilized after the season. Hence, the necessity to supplement nutrients in each subsequent year of plant vegetation was postulated. Fertigation was shown to require further improvement of the nutrient solution.